The Contribution Of Perceived Firm Marketing Innovation Initiatives To Customer Perceived Value And Loyalty: Does Switching Experience Really Matter? - Hui, Stephanie Wen Chuah; Marimuthu, Malliga; T. Ramayah, T. Ramayah (Asian Academy of Management (AAM), 2016)
In recent years, perceived frm marketing innovation initiatives (PFMII) are increasingly considered as an important means to ensure customers' continued loyalty. Although customer perceived value is believed to be a potential mediator between PFMII and customer loyalty, much of the evidence to date remains anecdotal or speculative. Furthermore, there is a dearth of knowledge about how the eﬀect of PFMII on customer value diﬀers between switchers and non-switchers. To bridge this knowledge gap, we propose a conceptual framework linking PFMII to customer perceived value and loyalty, and develop hypotheses about the moderating role of switching experience in some of these linkages. Data were collected from Generation Y(18–34 years old) who subscribed to post-paid mobile internet plans. The results showed that both functional and monetary values mediated the relationship between PFMII and customer loyalty. However, there was no signifcant diﬀerence in the eﬀect of PFMII on functional and monetary values between switchers and non-switchers. This research contributes to theory and practice by clarifying linkages between PFMII and customer loyalty by investigating the often widely neglected role of customer perceived value. In addition, this study successfully extended Sweeney